Training of Microbe Cell Visualization from Fermentation Food at UPT. Integrated Laboratory UHO - Muhamad Azwar Syah; Sapto Raharjo; La Ode Muhammad Iman Sulaiman; Jamili; Nasaruddin (Majalah Pengabdian Indonesia, 2024)
Indonesia has diverse local food commodities that are valuable as a national food source. Microbes serve an important part in food processing, but they can also be harmful and damage food products. The aim of this training is to provide students with skills in understanding microbial cell visualization techniques in food fermentation. Tempeh and the probiotic drink Yakult as sources of fungi and bacteria, respectively, were used in this training. There are four steps for this training consisting of preparation, visualization of mold on tempeh, visualization of bacteria on Yakult as well as training assessment. The findings indicate that students can identify the complex morphology of tempeh mold, which consists of aseptate hyphae, spores, and sporangiophores that sustain the sporangium. Moreover, they exhibited a bacil shape as the morphology of bacteria from Yakult under a light microscope with 400x magnification. Bacterial staining is recommended to visualize bacteria more clearly than without staining. This occurs because bacteria are smaller than mold and have a more translucent hue. The findings of the activity assessment revealed that participants were able to follow the instruction well. This is demonstrated by success indicators in displaying mold morphology, which includes hyphae, sporangiophores, sporangia, and spores. Participants were also able to identify the structure of rod-shaped bacterial organisms, known as bacilli.